Paucihalobacter ruber gen. nov., sp. nov., isolated from a haloalkaline lake sediment sample. Issue 10 (4th October 2020) - Wu, Shu-ge; Wang, Jing-jing; Wang, Jia-ning; Chen, Qi; Du, Zong-jun; Li, Yue-zhong
Abstract : A Gram-stain-negative, strictly aerobic, non-motile, rod-shaped bacterium, designated CWB-1 T, was isolated from a haloalkaline lake sediment sample collected from the bottom of Chaiwopu Lake, Urumchi, Xinjiang Province, PR China. Strain CWB-1 T grew at 4–40 °C (optimum, 30–35 °C), pH 6.5–9.0 (optimum, pH 6.5–7.0) and with 0.5–5.5 % (w/v) NaCl (optimum, 2.5–3.0 %). Phylogenetic analyses based on the 16S rRNA gene sequence and the whole genome sequence both revealed that strain CWB-1 T belonged to the family Flavobacteriaceae . The strain had the highest similarity of the 16S rRNA gene sequence to Psychroserpens jangbogonensis PAMC 27130 T (92.8 %). The genome of strain CWB-1 T was 3 548 011 bp long with 36.3 % DNA G+C content. The predominant fatty acids (>10 %) in the CWB-1 T cells were iso-C15 : 0, iso-C17 : 0 3-OH and summed feature 1 (iso-C15 : 1  H/C13 : 0 3-OH). The major respiratory quinone was menaquinone-6 and the major polar lipids were phosphatidylethanolamine, an unidentified aminolipid and two unidentified lipids. Based on the phylogenetic analyses, as well as the phenotypic characteristics, a novel genus and species of the family Flavobacteriaceae, Paucihalobacter ruber gen. nov., sp. nov., is proposed. The type strain is CWB-1 T (=KCTC 72450 T =CGMCC 1.17149 T ).